Geopolymer 3D printing: a comprehensive review on rheological and structural performance assessment, printing process parameters, and microstructure - Barve, Prasad; Bahrami, Alireza; Shah, Santosh (Frontiers in Materials, 2023)
Geopolymers are under scrutiny as a sustainable alternative to cement in 3D printing for eco-friendly construction. Geopolymer 3D Printing (G3DP) holds promise for green construction and advanced manufacturing. This study addresses G3DP's rheological properties, printability, and microstructure analysis. Results indicate the pivotal role of rheological properties in printability, encompassing parameters like pumpability, extrudability, and shape retention. Lower viscosity and appropriate yield stress are crucial. The structural performance of G3DP, given its inherent anisotropic nature and its assessment techniques, is scrutinized. Process variables such as nozzle design, print speed, and interval affect printability, buildability, and structural properties. Research on parameter optimization is necessary. Additionally, evaluation techniques for G3DP's rheological and structural behavior require standardization. Understanding G3DP's rheology is paramount for successful construction 3D printing. Findings offer quantitative insights into the importance of rheological properties for printability and structural performance. Microstructural analysis uncovers porosity and density disparities compared to traditional geopolymers. This comprehensive review provides valuable insights for researchers and practitioners to enhance G3DP's application as a futuristic sustainable construction material.